LINGUO-DIDACTIC CONTENT OF DISCURSIVE-STRATEGIC COMPETENCE OF LANGUAGE STUDENTS (Revista Inclusiones, 2020)
At the present stage of the development of the methods of teaching foreign languages, the problem of the formation of free speech communication in students occupies a special place. As the analysis of the development of foreign language teaching methods shows, this aspect has not been focused on for a rather long period. In the learning process, attention was most often paid to teaching all types of speech activity separately, which led to negative results in the context of achieving communicative goals. However, nowadays the situation has radically changed since the skills of free speech communication in a foreign language have become widely demanded primarily because of the social order and the needs of society. The increase in the volume and pace of information exchange and the accelerated development of computer communications have brought interaction in a foreign language to the forefront in the field of official communication and significantly strengthened its role in informal communication. In the article, we consider the process of developing discursive-strategic competence as an integral condition for the preparation of a competitive specialist.